Co-Occurrence of SARS-CoV-2 Infection and Inactivated SARS-CoV-2 Vaccination among Healthcare Workers - Cucunawangsih Cucunawangsih; Ratna Sari Wijaya; Nata Pratama Hardjo Lugito; Ivet Suriapranata (Case Reports in Infectious Diseases)
The presented cases describe the concurrent SARS-CoV-2 infection and inactivated SARS-CoV-2 vaccination among eight healthcare workers (HCWs). These cases highlighted the importance of broad hospital screening during the COVID-19 vaccination campaign. Further study regarding the durability of antibody response induced by infection and first-dose vaccination is required to determine the appropriate time for giving a second dose of inactivated SARS-CoV-2 vaccine among these cases.